Association of Increased Plasma Interleukin-6 and TNF-α Levels in Donors with the Complication Rates in Liver Transplant Recipients - Azarpira, N. (Avicenna Organ Transplantation Institute, 2013)
Background: Solid organ transplantation is the only definitive treatment available for patients with end-stage organ failure. Organs procured from brain-death donors are the main source of transplants. Following brain death, a burst of inflammatory reaction develops; it is characterized by increased plasma levels of cytokines. This inflammatory reaction has been associated with increased early allograft dysfunction. Objective: In this study, we test if the increased inflammatory response in brain-death donors is associated with more recipient complications. Methods: We prospectively recruited 38 consecutive brain-death donors admitted to the intensive care units (ICUs) of Shiraz University of Medical Sciences. Following the declaration of brain death, the demographics data on donor and recipient characteristics and cause of brain death were recorded. The post-liver transplant complications in recipients were stratified according to the Clavien classification. Plasma levels of cytokines IL-6, IL-2, and TNF-α were measured using enzyme linked immunosorbent assay (ELISA) kits, in all donors before organ procurement. Results: The mean (range) age of donors was 44 (16–74) years. Trauma due to car accident was the most common cause of brain death (79%). The post-liver transplant complications occurred in 19 (50%) recipients. The mean±SD plasma TNF-α concentration was significantly (p<0.001) higher in recipients with grade 1-3 post-transplant complications (68.33±27.74 pg/mL) than those without complication (22.09±4.14 pg/mL). Recipients with complications had also a significantly (p=0.001) higher mean±SD donor plasma concentration of IL-6 (1009±375.5 pg/mL) compared to those without complications (779±202 pg/mL). No significant differences was observed between the two groups in respect to IL-2 concentration (0.295±0.333 vs 0.285±0.342 U/mL, p=0.207). Six recipients died of complications (grade5), in whom no correlation could be found with donor plasma cytokine concentrations. Conclusion: Higher plasma concentrations of IL-6 and TNF-α in donors before organ procurement, are associated with more post-operative complications in liver transplant recipients.